The diagnostic value of fine needle aspiration in comparison with frozen section in thyroid nodules: A 20-year study - Sepideh Siadati; Seyed-mozafar Rabiee; Ebrahim Alijanpour; Mohammad-Ali Bayani; Novin Nikbakhsh (Babol University of Medical Sciences, 2017)
Background: Fine needle aspiration (FNA) is the most important method in the diagnosis of thyroid nodules before surgery. Recently, the efficiency of FNA in thyroid nodule management has been debatable. On the other hand, intraoperative frozen section (FS) has been used to confirm the diagnosis of FNA and select the proper surgical approach. In this regard, the present study aimed to assess the diagnostic value of FNA as compared to FS in the diagnosis of thyroid nodules. Methods: This retrospective study was performed on 69 patients with FNA and FS and histopathological examination from 1993 to 2014 in Babol, northern Iran. FNA was classified into 5 groups: benign (colloid goiter), lymphocytic thyroiditis, follicular lesions, suspicious and malignant, and FS was classified as after benign or malignant. The results of both methods were compared with each other. Results: This retrospective study was performed on 69 patients with FNA and FS and histopathological examination from 1993 to 2014 in Babol, northern Iran. FNA was classified into 5 groups: benign (colloid goiter), lymphocytic thyroiditis, follicular lesions, suspicious and malignant, and FS was classified as after benign or malignant. The results of both methods were compared with each other. Conclusion: FNA was considered as a simple, less invasive and cost effective method with fewer side effects for evaluation of thyroid nodules. Particulary it had a high sensitivity and specificity in experienced and skilled hands.